The Politics within the Histories We Write: Postcolonial Narrations of the Past in the Realm of Religion, Gender, and Education in Colonial Sri Lanka - Albrecht, Jessica A. (Religion & gender, 2024)
This article is a case study of Musaeus College, Colombo, especially its colonial past and the postcolonial histories written about it and its founder, Marie Musaeus Higgins. Marie Higgins, the founder of the school, is not only celebrated within the school, but also throughout the country as the mother of girls’ education. Strikingly, being a white woman coming from ‘the West’ to establish this school as well as some vernacular village schools and a teachers’ training college, is not criticised within postcolonial Sri Lanka as other imperial remains are. This article will look at exactly this opposition between the memory of Higgins today and the historical sources to illuminate the ways in which a present-day narration of the past is used to construct a postcolonial Buddhist-Sri Lankan identity within which contemporary issues of racialised religion are obscured by Buddhist nationalism.